Metrorrhagia: A Rare Manifestation of Anaphylaxis Induced by Allergen Immunotherapy - Ntakoula, Maria; Fokoloros, Christos; Chliva, Caterina; Papadavid, Evangelia; Makris, Michael (Archives of Clinical and Medical Case Reports, 2020)
Allergen specific immunotherapy is the only disease-modifying treatment for allergic rhinoconjuctivitis and asthma. We present a rare clinical case of metrorrhagia as the major manifestation of anaphylaxis induced by subcutaneous immunotherapy to inhalant allergens.